Monoclinic SrIrO3—a Dirac semimetal produced by non-symmorphic symmetry and spin–orbit coupling. (31st December 2018) - Takayama, T; Yaresko, A N; Takagi, H
Abstract: SrIrO3 crystallizes in a monoclinic structure of distorted hexagonal perovskite at ambient pressure. The transport measurements show that the monoclinic SrIrO3 is a low-carrier density semimetal, as in the orthorhombic perovskite polymorph. The electronic structure calculation indicates a semimetallic band structure with Dirac bands at two high-symmetry points of Brillouin zone only when spin–orbit coupling is incorporated, suggesting that the semimetallic state is produced by the strong spin–orbit coupling. We argue that the Dirac bands are protected by the non-symmorphic symmetry of lattice.